Assessment of indoor air quality in health clubs: insights into (ultra)fine and coarse particles and gaseous pollutants - Peixoto, Cátia; Pereira, Maria do Carmo; Morais, Simone; Slezakova, Klara (Frontiers in Public Health, 2023)
Introduction Exercising on regular basis provides countless health benefits. To ensure the health, well-being and performance of athletes, optimal indoor air quality, regular maintenance and ventilation in sport facilities are essential. Methods This study assessed the levels of particulate, down to the ultrafine range (PM10, PM2.5, and particle number concentration in size range of 20–1,000 nm, i.e., – PNC20-1000 nm), gaseous pollutants (total volatile organic compounds – TVOCs, CO2, and O3) and comfort parameters (temperature – T, relative humidity – RH) in different functional spaces of health clubs (n = 8), under specific occupancy and ventilation restrictions. Results and Discussion In all HCs human occupancy resulted in elevated particles (up to 2–3 times than those previously reported), considering mass concentrations (PM10: 1.9–988.5 μg/m3 PM2.5: 1.6–479.3 μg/m3) and number (PNC 1.23 × 103 – 9.14 × 104 #/cm3). Coarse and fine PM indicated a common origin (rs = 0.888–0.909), while PNC showed low–moderate associations with particle mass (rs = 0.264–0.629). In addition, up to twice-higher PM and PNC were detected in cardiofitness & bodybuilding (C&B) areas as these spaces were the most frequented, reinforcing the impacts of occupational activities. In all HCs, TVOCs (0.01–39.67 mg/m3) highly exceeded the existent protection thresholds (1.6–8.9 times) due to the frequent use of cleaning products and disinfectants (2–28 times higher than in previous works). On contrary to PM and PNC, TVOCs were higher (1.1–4.2 times) in studios than in C&B areas, due to the limited ventilations combined with the smaller room areas/volumes. The occupancy restrictions also led to reduced CO2 (122–6,914 mg/m3) than previously observed, with the lowest values in HCs with natural airing. Finally, the specific recommendations for RH and T in sport facilities were largely unmet thus emphasizing the need of proper ventilation procedures in these spaces.